Biopolymeric pellets of polyvinyl alcohol and alginate for the encapsulation of Ib-M6 peptide and its antimicrobial activity against E. coli - Flórez Castillo, J.M. (2019)
The encapsulation of Ib-M6 antibacterial peptide in pellets of polyvinyl alcohol (PVA) and polyvinyl alcohol-alginate (PVA-Alg) matrices was carried out in order to explore its controlled release and activity against Escherichia coli K-12. The pellets were obtained by combined ice segregation induced self-assembly (ISISA) and freezing-thawing methods and their microstructure was studied by scanning electron microscopy. Bromothymol blue was used as a model compound to study the transport mechanisms and release from pellets. The results show that there is a significant effect of the total concentration of PVA precursor solutions, the mass ratio of PVA of different molecular weights and the addition of alginate on the microstructure and transport properties of pellets. The antibacterial activity of Ib-M6 against Escherichia coli K-12 was not affected by the encapsulation in PVA pellets. However, the release of Ib-M6 from PVA-Alg pellets was not possible, probably due to the electrostatic interaction of positively charged Ib-M6 and negatively alginate structure. Nonetheless, the controlled release of Ib-M6 from polymeric matrices can be fitting by modifying parameters such as the concentration and type of polymer precursors.